Open-Switch Fault-Tolerant Control of a Grid-Side Converter in a Wind Power Generation System - Partha Sarati Das; Kyeong-Hwa Kim (International Journal of Power Electronics and Drive Systems (IJPEDS), 2015)
A fault-tolerant technique of a grid-side converter (GSC) is a very important task because the unbalanced grid power endangers the overall system. Since the GSC is very sensitive to grid disturbance, the complete system needs to be stopped suddenly once an open-switch fault occurs. To improve the reliability of system, the continuous operation should be guaranteed. In this paper, a redundant topology based fault-tolerant algorithm is proposed for a GSC in a wind power generation system. The proposed scheme consists of the fault detection and fault-tolerant algorithms. The fault detection algorithm employs the durations of positive and negaitive cycles of three-phase grid currents as well as normalized root mean square (RMS) currents. Once a fault is detected, the corresponding faulty phase is identified and isolated to enable the fault-tolerant operation. The faulty phase is replaced by redundant one rapidly to recover the original shape of the grid currents, which ensures the continuity in operation. In contrast with the conventional methods, the proposed fault detection and fault-tolerant algorithms work effectively even in the presence of the open faults in multiple switches in the GSC. Simulation results verify the effectiveness of the proposed fault diagnosis and fault-tolerant control algorithms.